Dispute Resolution in Commercial Law - in Light of Law No. 95.17 - Mohamed Fahfouhi (International Journal of Law Research and Studies, 2024)
Mechanisms for settling commercial disputes have become one of the manifestations of legal and economic thinking at world level, a desired tool for regulating and stimulating national and international trade, and an important and essential factor in increasing the flow of investment and alleviating the burden on the national judicial system, prompting the various countries - at the highest level - to attach great interest to this peaceful means. In this respect, the high speech of His Majesty King Mohammed VI on the occasion of the opening of the judicial year on 29 January 2003 in Agadir affirmed the following: ‘.... Thus, in accordance with Our firm desire to continue working to promote investment and in application of Our directives set out in the letter We sent to Our Prime Minister to this effect, we invite Our Government to continue its efforts to modernise the justice system, by rationalising work, simplifying procedures and ensuring the widespread use of information technology. It is also necessary to diversify the procedures for the consensual settlement of disputes that arise between partners in commercial transactions, by proceeding, with all due speed, to draw up a draft law on national and international commercial arbitration, which will enable our judicial system to meet the requirements of globalisation and economic competitiveness, and to help attract foreign investment’. In his speech on the occasion of the anniversary of the Revolution of the King and the People on 20 August 2009 in Tétouan, His Majesty added that: ‘...At the same time, alternative dispute resolution methods such as mediation, arbitration and conciliation should be developed, alternative sentences should be applied and local justice should be reviewed....’. Then the speech of 14 October 2022, which stated: ‘Today, we are banking on productive investment as an essential lever for reviving the national economy and anchoring Morocco in promising sectors’.